2022
DOI: 10.1111/jdv.18573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topical benzyl benzoate vs. oral ivermectin in treating scabies: A randomized study

Abstract: Human scabies is usually transmitted during skin-to-skin contact with persons infested with the ectoparasitic mite Sarcoptes scabiei var. hominis. Scabies is a rising major public health issue worldwide and has recently been designated as a neglected tropical disease by the World Health Organization (WHO). 1 Current guidelines propose a range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, as in some of our participants intensified applications of up to 8 weeks were necessary for cure, extension of treatment repetitions to three or more weeks might be considered to improve outcome in severe infestation. Several studies reported the successful treatment of permethrin‐refractory cases with alternative scabicides, such as benzyl benzoate 20% or ivermectin 9–11,13,35 . In our cohort, most patients were cured with a combination of permethrin 5% and ivermectin following the recommendations of the Austrian Society of Dermatology and Venereology 36 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, as in some of our participants intensified applications of up to 8 weeks were necessary for cure, extension of treatment repetitions to three or more weeks might be considered to improve outcome in severe infestation. Several studies reported the successful treatment of permethrin‐refractory cases with alternative scabicides, such as benzyl benzoate 20% or ivermectin 9–11,13,35 . In our cohort, most patients were cured with a combination of permethrin 5% and ivermectin following the recommendations of the Austrian Society of Dermatology and Venereology 36 .…”
Section: Discussionmentioning
confidence: 79%
“…Several studies reported the successful treatment of permethrin-refractory cases with alternative scabicides, such as benzyl benzoate 20% or ivermectin. [9][10][11]13,35 In our cohort, most patients were cured with a combination of permethrin 5% and ivermectin following the recommendations of the Austrian Society of Dermatology and Venereology. 36 Similarly, a recent study reported a better outcome with permethrin 5% plus ivermectin compared to the use of a single scabicide.…”
Section: Discussionmentioning
confidence: 99%
“…Since benzyl benzoate has been used infrequently in last decades preferring the faster acting and less irritant P5%, literature on its use in children is scarce, and the proposed schemes have varied. [12][13][14] After the reintroduction of BB25%, the duration of treatment was progressively reduced following its efficacy with shorter courses. At the same time, the number of applications required to obtain recovery with P5% progressively increased (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…This observation, along with reports of a rising incidence and decreased responsiveness to treatment of scabies emerging in the literature, 2–5 led us to increase the number of prescribed permethrin 5% applications and to reintroduce benzyl benzoate 25% as an alternative treatment. Since benzyl benzoate has been used infrequently in last decades preferring the faster acting and less irritant P5%, literature on its use in children is scarce, and the proposed schemes have varied 12–14 . After the reintroduction of BB25%, the duration of treatment was progressively reduced following its efficacy with shorter courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation